Eksposisi I Timotius 2:9-15 Terhadap Larangan Perempuan Yang Mengajar - Devi Maria Bunga (Institut Agama Kristen Negeri Kupang, 2021)
In carrying out the mission of the Great Commission of the Lord Jesus, every believer has the same role to carry it out. Regardless of gender or background, every believer has an equal position in the eyes of God to be directly involved in the field of church ministry without any restrictions. But in reality, there are still some churches that have not been able to accept a woman to be involved in all aspects of church ministry. This happens because there are still churches that assume wrongly about the position and role of women in the church. The purpose of this article is to provide a correct understanding of how to make Biblical truth relevant to the current situation regarding the prohibition of women teaching in the context of 1 Timothy 2: 9-15. The research method used a descriptive qualitative approach with the method of exposition of the biblical text. Christian women today can do any ministry in the church, but first understand God's calling in her and respond to it.